Detecting ionospheric anomalies associated with three Japan Miyako earthquakes to show their correlations and associated earthquake-induced tsunamis. Issue 1 (2nd January 2016) - Jyh-Woei, Lin
Abstract: This study employed two-dimensional principal component analysis (2DPCA) for the detection of anomalies in the two-dimensional ionospheric total electron content (TEC) associated with Japan three earthquakes and earthquake-induced tsunamis. From 04:40 to 04:50 (UTC) on February 15 th, first TEC precursor was detected over the epicentre of the 16 February quake with the duration time of at least 10 minutes. A weak TEC anomaly associated with an earthquake-induced tsunami was also detected from 23:15 to 23:20 (UTC) on 16 February with the duration time of at least 5 minutes. An additional earthquake ( Mw = 6.3) occurred in Miyako in the vicinity of the first earthquake. Second TEC precursor to the 20 February Miyako earthquake was recorded over the epicentre between 10:20 and 10:30 (UTC) on 19 February with the duration time of at least 10 minutes. A supplemental earthquake occurred ( Mw = 6.1) as well in Miyako in the vicinity of the first earthquake. A TEC precursor to the 21 February Miyako earthquake was recorded over the epicentre between 04:15 and 04:25 (UTC) on 20 February with the duration time of at least 10 minutes. The three Miyako earthquakes presented similar anomalies and duration time in the TEC fluctuations, due largely to similarities in the magnitudes of the largest principal eigenvalues and the close proximity of the epicentres. Our results led to the reasonable confirmation that the very weak TEC anomaly following the Miyako earthquake on 16 February was associated with the earthquake-induced tsunami. 2DPCA is a useful mathematical tool for the monitoring of anomalous ionospheric fluctuations for use in the early warning of weak tsunamis.